O cotidiano na cadeia pública de caraubas sob o olhar do agente penitenciário - Fonseca, Cristiana Cosmo (Universidade Federal Rural do Semi-Árido, 2017)
This research had the objective of analyzing the daily life of the penitentiary agent specifically in the Caraúbas Public Chain - CPC, located in Caraúbas-RN. It is characterized as a case study, qualitative approach and descriptive nature. As methods of collection of research were used the semi-structured interview and the participant observation with the penitentiary agents. The analytical strategy used was the analysis of content and it is possible to analyze the daily routine of prison staff, their perception of the prison system, and their working conditions: physical, equipment and psychic structure. The information collected showed that the working conditions of the prison staff in the CPC are deficient, mainly due to the lack of adequate infrastructure; the physical structure is not good contributing to the day-to-day insecurity, and together with the lack of equipment necessary for the proper functioning of the service. The psychic conditions are also not favorable; the work in the jail provokes a series of emotions that harm the physical and mental health of the penitentiary agent reaching also the familiar conviviality.
Monografia
Keywords: Sistema penitenciário; Agente penitenciário; Condições de trabalho; Penitentiary system; Prison guard; Work conditions; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO